The Association between Prosocial Behaviour and Peer Relationships with Comorbid Externalizing Disorders and Quality of Life in Treatment-Naïve Children and Adolescents with Attention Deficit Hyperactivity Disorder - Szabina Velő; Ágnes Keresztény; Gyöngyvér Ferenczi-Dallos; Luca Pump; Katalin Móra; Judit Balázs (Brain Sciences, 2021)
Several recent studies confirmed that Attention Deficit Hyperactivity Disorder (ADHD) has a negative influence on peer relationship and quality of life in children. The aim of the current study is to investigate the association between prosocial behaviour, peer relationships and quality of life in treatment naïve ADHD samples. The samples included 79 children with ADHD (64 boys and 15 girls, mean age = 10.24 years, SD = 2.51) and 54 healthy control children (30 boys and 23 girls, mean age = 9.66 years, SD = 1.73). Measurements included: The “Mini International Neuropsychiatric Interview Kid; Strengths and Difficulties Questionnaire” and the “Inventar zur Erfassung der Lebensqualität bei Kindern und Jugendlichen”. The ADHD group showed significantly lower levels of prosocial behaviour and more problems with peer relationships than the control group. Prosocial behaviour has a weak positive correlation with the rating of the child’s quality of life by the parents, both in the ADHD group and in the control group. The rating of quality of life and peer relationship problems by the parents also showed a significant negative moderate association in both groups. The rating of quality of life by the child showed a significant negative weak relationship with peer relationships in the ADHD group, but no significant relationship was found in the control group. Children with ADHD and comorbid externalizing disorders showed more problems in peer relationships than ADHD without comorbid externalizing disorders. Based on these results, we conclude that therapy for ADHD focused on improvement of prosocial behaviour and peer relationships as well as comorbid externalizing disorders could have a favourable effect on the quality of life of these children.